PENGARUH KONSUMSI TELUR AYAM RAS REBUSTERHADAP PENINGKATAN KADAR HB PADA IBU HAMIL TRIMESTER III DI PUSKESMAS SIMARMATAKABUPATEN SAMOSIR 2020 - Tetty Junita Purba (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
The period of pregnancy is a time when the body really needs maximum food intake for both the mother and the fetus.During pregnancy, there will be major changes in the body of a pregnant woman. One of the changes that occurs is the hematology system, with a lack of quality food intake, one of which is a lack of iron so that it can cause anemia in pregnant women. Anemia occurs due to low hemoglobin levels in the body of pregnant women. One of the efforts that can be done is to increase hemoglobin by consuming boiled eggs. The purpose of this research was to determine the effect of consumption of boiled chicken eggs at the Simarmata Health Center, Samosir Regency.Its benefits are to help pregnant women who have anemia so that the hemoglobin in the body of pregnant women increases, so that pregnant women are expected to consume boiled eggs in the third trimester of pregnancy. The population in this study were pregnant women in the area of the Simarmata Health Center, Samosir Regency, with a sample of 20 people. The research method was quasi-experimental (Quasi experiment) with a pre-test-post-test research design with a control group. The results of this study indicate that the average before consumption of boiled eggs is Mean (8.08) with Std. Deviation (0.5716) after consumption of boiled eggs is (9.39) with Std. Deviation0.5716) after Consumption of Boiled Eggs is (9.39) with Std. Deviation (0.5558) with sig <0.05, this indicates that there is an effect of consumption of boiled eggs on changes in hemoglobin levels for pregnant women in trimester III.